2018
DOI: 10.1111/ncn3.12237
|View full text |Cite
|
Sign up to set email alerts
|

Frontal executive function and the bladder: A study of dementia with Lewy bodies

Abstract: Background: Pathophysiology of bladder dysfunction in dementia with Lewy bodies (DLB, a disease that shares pathology with Parkinson's disease [PD]) is disturbed prefrontal-basal ganglia pathway. Similarly, DLB/PD patients have frontal executive dysfunction by the same mechanism. Aim: To study the relationship between executive function and bladder autonomic function in patients with DLB. Methods: We recruited 45 patients with DLB (28 male, 17 female; age 73.3 years AE 6.8). Other neurologic, urologic, and sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Clinical studies have shown that in elderly subjects with urodynamic detrusor overactivity and OAB symptoms, the OAB was not closely associated with general cognitive task (as measured by the Mini-Mental State Examination [MMSE]) but was closely associated with an inhibitory control task (a category of the Frontal Assessment Battery [FAB], a function of decision-making), indicating that a loss of general inhibition by the PFC lesion may lead to both OAB and disturbed decision-making [77]. Similar findings were observed in another investigation [78].…”
Section: Brain Area Relevant To the Luts: Cortical Structuressupporting
confidence: 69%
“…Clinical studies have shown that in elderly subjects with urodynamic detrusor overactivity and OAB symptoms, the OAB was not closely associated with general cognitive task (as measured by the Mini-Mental State Examination [MMSE]) but was closely associated with an inhibitory control task (a category of the Frontal Assessment Battery [FAB], a function of decision-making), indicating that a loss of general inhibition by the PFC lesion may lead to both OAB and disturbed decision-making [77]. Similar findings were observed in another investigation [78].…”
Section: Brain Area Relevant To the Luts: Cortical Structuressupporting
confidence: 69%